Sifat Optik dan Energi Gap Film Ferroelektrik LiTaSiO5 di Atas Substrat Silikon - La Isa; . Irmansyah; . Irzaman (Institut Pertanian Bogor, 2016)
Lithium tantalate silicate (LiTaSiO5) has successfully been made on Si (100) p-type and Si (111) n-type by chemical solution deposition (CSD) technique with temperatures variation of 600, 650, 700, 750, and 800 oC. Determined the film thickness as well as and test the optical properties with UV-Vis spectroscopy. The maximum absorbance of the substrates were 420 and 980 nm. The maximum band of films on Si (100) was 2.94 eV a temperature of 650 oC and Si (111) was 3.06 eV a temperature of 800 oC